2016
DOI: 10.1002/ajmg.a.37838
|View full text |Cite
|
Sign up to set email alerts
|

“It wasn't a disaster or anything”: Parents’ experiences of their child's uncertain chromosomal microarray result

Abstract: Chromosomal microarray is an increasingly utilized diagnostic test, particularly in the pediatric setting. However, the clinical significance of copy number variants detected by this technology is not always understood, creating uncertainties in interpreting and communicating results. The aim of this study was to explore parents' experiences of an uncertain microarray result for their child. This research utilized a qualitative approach with a phenomenological methodology. Semi-structured interviews were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 39 publications
3
42
0
Order By: Relevance
“…Doctors were hesitant to assign causality, with only 6% of those letters referring to the VUS as the main explanation for the patient's symptoms. Interestingly, previous studies have found that parents of children diagnosed with a VUS are likely to assign cause to the finding, 22 even following a consultation with a VCGS genetics specialist 23,24 where they would likely have received a summary letter. Studies have also found that many parents experience a sense of relief once they know 'the reason' for their child's problems, even when the result is a VUS, and that they felt it helped them to accept their child's symptoms.…”
Section: Discussion Of Causal Uncertaintymentioning
confidence: 99%
See 4 more Smart Citations
“…Doctors were hesitant to assign causality, with only 6% of those letters referring to the VUS as the main explanation for the patient's symptoms. Interestingly, previous studies have found that parents of children diagnosed with a VUS are likely to assign cause to the finding, 22 even following a consultation with a VCGS genetics specialist 23,24 where they would likely have received a summary letter. Studies have also found that many parents experience a sense of relief once they know 'the reason' for their child's problems, even when the result is a VUS, and that they felt it helped them to accept their child's symptoms.…”
Section: Discussion Of Causal Uncertaintymentioning
confidence: 99%
“…Studies have also found that many parents experience a sense of relief once they know 'the reason' for their child's problems, even when the result is a VUS, and that they felt it helped them to accept their child's symptoms. 23,24 The 'newness of microarray testing' Describing CMA testing as 'new' occurred in letters written from 2010 to 2013 and by seven individual doctors. This language is consistent with a previous study which found doctors use statements such as 'this testing is still new' in order to provide context for the patient/family regarding the source of uncertainty.…”
Section: Discussion Of Causal Uncertaintymentioning
confidence: 99%
See 3 more Smart Citations